Pengaruh Standar Operasional Prosedur Dan Loyalitas Kerja Terhadap Produktivitas Kerja Karyawan CV. Wild Outdoor Tasikmalaya - Zaki Abdussalam; Suci Putri Lestari; Kusuma Agdhi Rahwana (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2023)
This study aims to determine the effect of standard operating procedures and job loyalty on employee productivity at CV. Outdoor Tasikmalaya. The research method used is quantitative method through causality method with survey approach. The data used used primary and secondary with a research sample of 65 respondents based on 65 existing population data. The analytical tool used is multiple linear regression. The test results show that standard operating procedures and job loyalty simultaneously have a significant effect on work productivity. Standard operating procedures partially have a significant effect on work productivity, work loyalty partially has a significant effect on work productivity.